Interculturalidad y Aprendizaje Significativo - Cárdenas Chafla, Sandro David (2025)
The objective of this research is to propose a guide of strategies for interculturality and meaningful learning in sixth semester students of Basic Education at the National University of Chimborazo UNACH. The methodology was developed through mixed research, for this purpose, surveys of 10 questions were applied, which addressed key points on interculturality and meaningful learning, the study population were 34 students belonging to the career of Basic Education of the UNACH. The design was non-experimental where the variables were not manipulated, making this an exploratory and descriptive research. The results obtained were analyzed by means of tables and graphs where the answers to each question were represented, thus identifying the results, which show a positive and majority perspective regarding interculturality, its respect and support. In this study it was possible to detect the importance of interculturality, as well as the challenges and needs for cultural interaction, and the relevance of updating pedagogical strategies to promote an inclusive educational environment and respect for cultural diversity. In conclusion, it is of great importance to design a guide based on thoughts and knowledge about interculturality in the studied population group, as well as the need to integrate current methodologies with innovative and relevant pedagogical approaches for cultural interaction in the classroom and finally to integrate continuous practice on the part of the students.